Patient reported outcome measures in military patients with shoulder instability. Issue 4 (22nd March 2013) - Middleton, Simon; Guyver, P; Boyd, M; Brinsden, M
Abstract : Objectives: The Oxford Shoulder Instability Score (OSIS) is a measure of functional impairment of the upper limb, but it is unclear how it translates into military patients where lower scores, implying higher function, may still be insufficient to meet the increased demands of military service and necessitating surgery. This study aimed to compare OSIS in military and civilian patients undergoing shoulder stabilisation surgery. Methods: We undertook a prospective, blinded cohort-controlled study with a null hypothesis that there was no difference in the Oxford Instability Scores between military and civilian patient groups. 40 patients were required in each group. A prospective clinical data base (iParrot, ByResults, Oxford, UK) was interrogated for consecutive patients undergoing shoulder stabilisation surgery at a single centre. The senior author—blinded to the outcome score—matched patients according to age, gender and diagnosis. Statistical analysis showed the data to be normally distributed and a paired samples t test was used to compare the two groups. Results: 110 patients were required to provide a matched cohort of 40 in each group (70 male, 10 female subjects). Age distribution was 16–19 years (n=6); 20–24 years (n=28); 25–29 (n=16); 30–34 (n=12); 35–49 (n=12); and 40–44 (n=6). 72 patients (90%) had polar group 1 instability and eight patients (10%) had polar group 2 instability. The mean OSIS in the civilian group was 17.25 and in the military group 18.25. There was no statistical difference between the two groups (p=0.395). Conclusions: This study supports the use of the OSIS to assess military patients with shoulder instability and monitor the progress of their condition.